Intensive Management of Diffuse Peritonitis Caused by Spontaneously Healed Gastric Perforation: A Case Report - Liliriawati Ananta Kahar; Wiwi Monika Sari; Ridho Prasetiawan; Kahfi Rakhmadian; Prima Yudi Leo (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Gastric perforation will cause acute peritonitis. Proper diagnosis and management, especially in ICU, are needed to prevent complications and even death from this event. This study aimed to describe the intensive management of diffuse peritonitis caused by gastric perforation. Case presentation: A 61 years old male patient presented with pain in the whole abdomen for 6 days before admission. The pain began at the epigastrium and suddenly spread to the whole abdomen. The pain was felt continuously and increased by movement. Routine blood examination revealed anemia, lekousitosis, and radiology examination found homogeneous confluence was found in the abdominal, dilated small intestine, psoas line was not visible, in the left lateral decubitus position, an air-fluid level and free air were found. The patient underwent diagnostic laparoscopic surgery + peritoneal lavage on emergency surgery for 2 hours, obtained a resolution of gastric perforation, and the patient was treated postoperatively in the ICU of Dr. M. Djamil General Hospital. Conclusion: Cases of spontaneous resolution of gastric perforation are not only in terms of surgical management but in terms of postoperative care. It also plays an important role in the success and good results in cases of gastric perforation.